STRATIGRAPHY OF RHAETIAN TO LOWER SINEMURIAN CARBONATE PLATFORMS IN WESTERN LOMBARDY (SOUTHERN ALPS, ITALY): PALEOGEOGRAPHIC IMPLICATIONS - FLAVIO JADOUL; MARIA TERESA GALLI; LORENZO CALABRESE; MARIO GNACCOLINI (Rivista Italiana di Paleontologia e Stratigrafia, 2005)
A stratigraphical revision of the Upper Triassic-Lower Jurassic succession of the western Southern Alps (Varese area) leads to the introduction of one new lithostratigraphical unit: the ?upper Hettangian-lower Sinemurian Alpe Perino Limestone and the recognition, also in the western Lombardy, of the Rhaetian Zu Limestone, consisting of subtidal cycles, with inner platform facies at the base (Campo dei Fiori Dolomite). These formations represent lagoonal-peritidal to subtidal carbonate depositional systems. A locally angular unconformity between the Rhaetian (or the lower Hettangian) and the upper Hettangian-Sinemurian formations, characterised by ‘terra rossa’ paleosols and pedogenetic carbonate breccias, can be correlated through all of the investigated profiles. The Lower Jurassic paleogeography of the western Lombardy Basin was characterised by an emerged area from Hettangian until earliest Sinemurian times in a warm humid paleoclimate. The Alpe Perino Limestone represents a small peritidal to subtidal carbonate platform developed only in a shallow-water gulf of the M. Nudo area. The platform was surrounded by a wide emerged area (island or peninsula ?), in the west to southeast, and by open subtidal and basinal environments, in the east to northeast (M. Generoso basin).